Quantitative methods in reservoir engineering - Chin, Wilson C. (Amsterdam ; Boston : Gulf Professional Pub., 2002)
For the practitioner, this volume is a valuable tool for predicting reservoir flow in the most efficient and profitable manner possible, using quantitative methods rather than anecdotal and outdated methods. For the student, this volume offers insight not covered in other textbooks. Too many approaches in traditional petroleum engineering are based on "ad hoc" and "common sense" methods that have no rigorous mathematical basis. Most textbooks dealing with reservoir engineering do not go into the necessary mathematical detail and depth. This new book by Wilson Chin, a revision of two earlier books published by Gulf Publishing, Modern Reservoir Flow and Well Transient Analysis and Formation Invasion, integrates rigorous mathematical methods for simulating and predicting reservoir flow both near and away from the well. Predicts reservoir flow to maximize resources, time, and profits Includes problems and solutions for students Presents mathematical models in an easy-to-understand and easy-to-simulate format.
Motivating ideas and governing equations -- Fracture flow analysis -- Flows past shaly bodies -- Streamline tracing and complex variables -- Flows in complicated geometries -- radial flow analysis -- Finite difference methods for planar flows -- Curvilinear coordinates and numerical grid generation -- Steady-state reservoir applications -- Transient compressible flows : numerical well test simulation -- Effective properties in single and multiphase flows -- Modeling stochastic heterogeneities -- Real and artificial viscosity -- Borehole flow invasion, lost circulation, and time lapse logging -- Horizontal, deviated, and modern multilateral well analysis -- Fluid mechanics of invasion -- Static and dynamic filtration -- Formation tester applications -- Analytical Methods for Time Lapse Well LoggingAnalysis -- Complex invasion problems : numerical modeling -- Forward and inverse multiphase flow modeling.
Includes bibliographical references (p. 453-461) and index.
Keywords: Oil reservoir engineering; Electronic books